Mail and guardian . The weekly mail : the paper for a changing South Africa
(1985) - (1992) titled: The weekly mail. The paper for a changing South Africa; (1993) titled: The weekly mail. Publ. with the Guardian weekly.; (1994) - (1995) titled: Weekly mail and guardian